THE INFLUENCE OF QUALITY AND PRICE ON PURCHASE DECISIONS OF MUSLIM CLOTHES IN INDAH BORDIR SIDOARJO - Qoriani, Hersa Farida (Tijarah: Jurnal Ekonomi Syariah, 2023)
Islam teaches how to dress neatly and politely, with the intention that we are kept away from evil and the punishment of Allah SWT. The purpose of this study was to analyze partially, simultaneously between quality, price on purchasing decisions, quantitative research, population 115,250 and sample 100. The results show that quality and price have an influence on purchasing decisions. With the value of X1 = significant 0.001 0.05 and the value of t count 3.124 t table 1.660., X2 = significant 0.000 0.05 and the value of t count 8.399 t table 1.660. simultaneously has a significant effect of 0.000 0.05 and the value of F = 24.071 3.687